Clathrin-Mediated Endocytosis Delivers Proteolytically Active Phytaspases Into Plant Cells - Trusova, Svetlana V.; Teplova, Anastasia D.; Golyshev, Sergei A.; Galiullina, Raisa A.; Morozova, Ekaterina A.; Chichkova, Nina V.; Vartapetian, Andrey B. (Frontiers in Plant Science, 2019)
Phytaspases belong to the family of plant subtilisin-like proteases and are distinct from other family members, as they have strict and rarely occurring aspartate cleavage specificity and unusual localization dynamics. After being secreted into the apoplast of healthy plant tissues, phytaspases are able to return back into cells that have been committed to cell death due to a variety of biotic and abiotic stresses. It was recently discovered that retrograde transport of phytaspases involves clathrin-mediated endocytosis. To examine what happens to the proteolytic activity of phytaspases upon internalization, and determine whether endocytic uptake of phytaspases is a specific event, two experimental approaches were here employed. In the first one, Nicotiana tabacum phytaspase-EGFP protein (NtPhyt-EGFP) was transiently produced in Nicotiana benthamiana leaves, and consequences of the NtPhyt-EGFP internalization caused by antimycin A-induced oxidative stress were studied. In the second approach, the behavior of Arabidopsis thaliana phytaspase-EGFP protein (AtPhyt-EGFP) that was spontaneously internalized when transiently produced in N. benthamiana leaves was addressed. We demonstrated that phytaspase internalization, whether stress-induced (for NtPhyt) or spontaneous (for AtPhyt), is accompanied by re-distribution of phytaspase activity from the apoplast to the cell interior. Inhibition of clathrin-mediated endocytosis by co-production of the Hub protein prevented phytaspase internalization and phytaspase activity re-localization. For AtPhyt-EGFP spontaneously internalized into healthy N. benthamiana cells, the presence of a proteolytically active enzyme inside the cells for an approximately 2-day time period was observed before the phytaspase degraded. Specificity of endocytic uptake of phytaspases was demonstrated by the co-production of an apoplast-targeted mRFP protein marker. This marker retained its apoplastic localization when phytaspase internalization was essentially complete. Our data, therefore, point to clathrin-mediated endocytosis as a means to deliver proteolytically active phytaspases into plant cells. The specificity of phytaspase internalization suggests that a phytaspase receptor may be present at the plasma membrane of plant cells. It would be interesting in the future to identify this putative receptor, as well as to learn whether or not phytaspases are unique among the large family of plant subtilisin-like proteases in their ability to utilize retrograde trafficking.